MicroRNAs Are Essential for Stretch-induced Vascular Smooth Muscle Contractile Differentiation via MicroRNA (miR)-145-dependent Expression of L-type Calcium Channels - Turczyńska, Karolina M. (American Society for Biochemistry and Molecular Biology, 2012)
Stretch of the vascular wall is an important stimulus to maintain smooth muscle contractile differentiation that is known to depend on L-type calcium influx, Rho-activation, and actin polymerization. The role of microRNAs in this response was investigated using tamoxifen-inducible and smooth muscle-specific Dicer KO mice. In the absence of Dicer, which is required for microRNA maturation, smooth muscle microRNAs were completely ablated. Stretch-induced contractile differentiation and Rho-dependent cofilin-2 phosphorylation were dramatically reduced in Dicer KO vessels. On the other hand, acute stretch-sensitive growth signaling, which is independent of influx through L-type calcium channels, was not affected by Dicer KO. Contractile differentiation induced by the actin polymerizing agent jasplakinolide was not altered by deletion of Dicer, suggesting an effect upstream of actin polymerization. Basal and stretch-induced L-type calcium channel expressions were both decreased in Dicer KO portal veins, and inhibition of L-type channels in control vessels mimicked the effects of Dicer deletion. Furthermore, inhibition of miR-145, a highly expressed microRNA in smooth muscle, resulted in a similar reduction of L-type calcium channel expression. This was abolished by the Ca(2+)/calmodulin-dependent protein kinase II inhibitor KN93, suggesting that Ca(2+)/calmodulin-dependent protein kinase IIδ, a target of miR-145 and up-regulated in Dicer KO, plays a role in the regulation of L-type channel expression. These results show that microRNAs play a crucial role in stretch-induced contractile differentiation in the vascular wall in part via miR-145-dependent regulation of L-type calcium channels.